Valuation of Intrinsic Value of Construction Sector Stock Using Residual Income Model (RIM) and Dividend Discount Model (DDM) - Dwi Yulianto; Sri Mulyantini; Dianwicaksih Arieftiara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine and analyze the intrinsic value valuation, consistency and influence of the intrinsic value of the shares of construction sector companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. The sample selection technique used in this study is full sampling and obtained as many as 12 companies with a total number of research samples is 48 samples. The data analysis technique used in this research is descriptive analysis using Microsoft Excel 2016 software and hypothesis testing was carried out using Panel Data Regression Analysis using E-Views version 9.0 software with a significance level of 5%. The results obtained in this study are (1) Based on the results of the consistency test carried out on the research sample using the Residual Income Model (RIM) and Dividend Discount Model (DDM) methods, the results of the consistency percentage are 47.92% consistent and 52.08 % inconsistent. (2) The intrinsic value of the shares calculated using the RIM method has no effect on the share price. (3) The intrinsic value of shares calculated using the DDM method has a positive and significant effect on stock prices.”